As limitações aos direitos fundamentais: os limites dos limites como instrumento de proteção ao núcleo essencial destes direitos - Denny Mendes Santiago (2012)
The promulgation of the Constitution of 1988 inserted Brazil into the Democratic Rule-of- Law State paradigm. Thenceforth, fundamental rights play an important role in the legal structure as central norms in the constitutional system. Due to this new function, a closer study of this subject is required not only by scholars but also by decision makers responsible for their implementation. Therefore, Constitutional law hermeneutics has inaugurated an effort of understanding the dynamics of these rights in order to make them as effective as possible and to prevent any form of distortion in their content. Nonetheless, Constitutional hermeneutics can only perform the function of optimizing and protecting fundamental rights if the theme of limiting fundamental rights is duly understood by legal science. Since it is not possible to interpret fundamental rights as being absolute and unlimited, due to social and economic interests involved, understanding how the process of limiting these rights functions is a task of major importance in order to ensure that they are not endangered by contingencies and casuistry. Thus, the activity of limiting fundamental rights must be developed in a way they are not perverted or diminished. This present dissertation will analyze theories that support and legitimate the notion that fundamental rights can be limited under constitutionally justified grounds, in order to understand how the process of limiting fundamental rights works legally, so that the outlines of this process can be identified. Constitutional hermeneutics ought to establish criteria for the activity of limiting fundamental rights; one of these criteria is the assurance that these rights have their essential content preserved when limited. Hence, limits are necessary to the activity of limiting rights, as described by German jurists in the Schranken-Schranken theory. The present work aims to identify what are these limits to the limiting activity to fundamental rights, to identify juristic fundaments that can instrumentalize the limits to limiting theory.